2015
DOI: 10.1111/jgs.13611
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reported Memory Failures: Associations with Future Dementia in a Population‐Based Study with Long‐Term Follow‐Up

Abstract: Self-reported memory failure predicted future dementia or AD independent of objective memory performance. Subjective reports of complaints by family and friends appear to be an even more-important indicator of preclinical impairments, and physicians should not ignore them, even in the absence of objective memory deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 40 publications
3
25
1
Order By: Relevance
“…The question of whether self or informant reports are more predictive of future cognitive decline is complex, and depends on the time of the assessment. In contrast to some previous studies suggesting informant reports to be more predictive [2,17,42] when assessing self and informant reports simultaneously, our study found self-reports to be more accurate in predicting future cognitive change. Our older sample was cognitively healthy but at risk, whereas most previous studies were based on memory-clinic patients or persons with MCI.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The question of whether self or informant reports are more predictive of future cognitive decline is complex, and depends on the time of the assessment. In contrast to some previous studies suggesting informant reports to be more predictive [2,17,42] when assessing self and informant reports simultaneously, our study found self-reports to be more accurate in predicting future cognitive change. Our older sample was cognitively healthy but at risk, whereas most previous studies were based on memory-clinic patients or persons with MCI.…”
Section: Discussioncontrasting
confidence: 99%
“…In clinical settings self-reports are often associated with actual cognitive test performance among healthy controls, but among patients with mild cognitive impairment informant reports are more often associated with cognition [15,16]. In a population-based study [2] both self-reported SMCs and informant reports predicted future dementia or AD, independent of objective memory performance across 10-12 years follow-up time. In a non-demented clinical sample, informant complaints improved accuracy of the Mini Mental State Examination (MMSE) in predicting probable AD over 2 years but patient complaints did not [17].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Given that elderly people with AD usually experience SCD prior to the onset of dementia, SCD has been regarded as the earliest stage in the continuous progression to AD (Reisberg et al, 2008;Hafkemeijer et al, 2013). Subjective decline in memory vs. in other cognitive domains could result in a higher risk of conversion to subsequent aMCI or AD (Rönnlund et al, 2015;Buckley et al, 2016). A recent review has shown that compared with age-matched controls, individuals with SCD suffered a 4.5-fold higher risk of progressing to subsequent MCI, and the risk of eventual progression to AD increased by 6.5-fold (Lin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of older people, subjective memory complaints have been particularly associated with the management of daily living activities and perceived quality of life, and they have been studied as possible indicators of cognitive decline, mild cognitive impairment (MCI) and even dementia (e.g., Farias et al, 2009; Hong et al, 2014; Juncos-Rabadan et al, 2012; Maki et al, 2014; Montejo et al, 2012; Ogata et al, 2015; Rönnlund et al, 2015a; Rönnlund et al, 2015b; Waldorff et al, 2012). Despite the great importance of subjective memory complaints in elderly populations, the characterization of the same phenomenon in younger groups is also relevant to explore how memory changes are perceived across development, and how this self-report can be used in the evaluation of memory difficulties in specific age groups (Ginó et al, 2010; Pearman, 2009).…”
Section: Introductionmentioning
confidence: 99%